Tissue Culture and Somatic Embryogenesis in Warm-Season GrassesCurrent Status and Its Applications: A Review - Melody Ballitoc Muguerza; Takahiro Gondo; Genki Ishigaki; Yasuyo Shimamoto; Nafiatul Umami; Pattama Nitthaisong; Mohammad Mijanur Rahman; Ryo Akashi (My University, 2022)
Warm-season grasses are C4 plants and have a high capacity for biomass productivity. These grasses are utilized in many agricultural production systems with their greatest value as feeds for livestock, bioethanol, and turf. However, many important warm-season perennial grasses multiply either by vegetative propagation or form their seeds by an asexual mode of reproduction called apomixis. Therefore, the improvement of these grasses by conventional breeding is difficult and is dependent on the availability of natural genetic variation and its manipulation through breeding and selection. Recent studies have indicated that plant tissue culture system through somatic embryogenesis complements and could further develop conventional breeding programs by micropropagation, somaclonal variation, somatic hybridization, genetic transformation, and genome editing. This review summarizes the tissue culture and somatic embryogenesis in warm-season grasses and focus on current status and above applications including the author's progress.
Keywords: Somaclonal variation; Asexual reproduction; Apomixis; Plant Taxonomy and Phylogenetics